Analysis of a novel soft switching bidirectional DC-DC converter for electric vehicle - Podila Purna Chandra Rao; Radhakrishnan Anandhakumar; L. Shanmukha Rao (Institute of Advanced Engineering and Science, 2023)
A bidirectional converter (BDC) designed with high voltage gain and it is incorporated with the soft-switching operations to the insulated gate bipolar transistors (IGBTs). The main dual operating characteristics of this converter are boost and buck modes respectively. In order to achieve the reduced switching losses and improved efficiency, the main IGBTs are operated at zero current (ZC) while the IGBTs commutating from turn-on to turn-off state. The ZC turn-off operation is obtained with the aid of soft- switched cell, which consists of resonant inductor (Lr), capacitor and additional IGBTs. In this work, the design simulation analysis for high-gain BDC was performed by 70/300 V power system with the maximum 800 W output power under the operating frequency of 50 kHz. The efficiency for the high-gain soft-switched BDC was obtained as 96.5% when it is operating in boost mode and efficiency of 97% was achieved for the buck mode operation. The simulation evaluations of the above said converters were performed by using MATLAB/Simulink.